A Simple Information System Using Spreadsheets For Inpatient Daily Census (Si-Sehari) Of Klungkung District General Hospital: Sistem Informasi Sederhana Menggunakan Spreadsheet Untuk Sensus Harian Rawat Inap (Si-Sehari) Rumah Sakit Umum Daerah Kabupaten Klungkung - Wardana, I Wayan Dody Putra; Mahardika, I Made; Sudarsana, I Gede Diki (Universitas Muhammadiyah Sidoarjo, 2025)
Daily census reporting is something carried out by hospitals to describe the achievements of inpatient service quality indicators. Based on Minister of Health Regulation Number 1171 of 2011 concerning Hospital Information Systems, it is stated that the daily inpatient census is included in the Recapitulation Report 3 reporting regarding inpatient service activity data. Based on a preliminary study conducted at the Klungkung Regional General Hospital, it is known that the implementation of the daily census uses a manual system, causing several problems, namely late reporting of daily records, frequent recording errors, loss of daily census forms and lack of flexibility in filling them out. Therefore, a simple Spreadsheet-based information system innovation (Si-Sehari) is needed to overcome problems that arise during the implementation of the daily census. This research was carried out to determine the stages and process of implementing a simple Spreadsheet-based information system design (Si- Sehari) for the daily inpatient census at Klungkung Regency Regional Hospital. The method used is quasi-experimental with the development method being the waterfall method. With the development of Si-Sehari, there are good implications for the implementation of inpatient service reporting. All users stated that using this information system provides convenience in its implementation including easy access, flexible filling and changing of data, easy search for data, cost efficient and effective in use. Thus, the use of the Si-Sehari Spreadsheet system improves the quality of hospital services, especially reporting to hospital management in real time.